Imaginaries of and in Svalbard: The 'making' of an archipelago - Albert, Mathias; Brode-Roger, Dina; Iversen, Lisbeth (Palgrave Macmillan, 2023)
Albert M. Imaginaries of and in Svalbard: The 'making' of an archipelago. In: Albert M, Brode-Roger D, Iversen L, eds. Svalbard Imaginaries: The Making of an Arctic Archipelago . Cham: Palgrave Macmillan; 2023: 1-16.